Domestic Wastewater Treatment by Multiple Layer Media Filter - Sangwijit, Chonyitree; Sangwijit, Prapagon (Frontiers in Engineering Innovation Research, 2020)
This research was a quasi-experimental research. The objective was to apply 3 types of media, which were oyster shells, concrete rubbish, and zeolites, which were scrap materials that were easy to found for treating domestic wastewater. The medium was contained in layers vertically in parallel. Wastewater was continuous with 19 Watt pump, the flow rate of 13 liters per minute, the hydraulic retention time of 6 days and compares the efficiency of the wastewater treatment by multiple layers between media and without media. The results showed that wastewater treatment by multiple layers with media could treat total suspended solids and orthophosphate well with the highest removal efficiency, the hydraulic retention time of 6 was 100 and 86.78%, respectively. Wastewater treatment system using layers without media can treat fat and oil well with the highest removal efficiency, the hydraulic retention time of 6 was 39.8%. Both wastewater treatments by multiple layers with media and without media. The removal efficiency of COD was not different. With statistical significance at the level of 0.05.